NOTE ON A PRELIMINARY EXPERIMENT ON THE CULTURE OF SILLAGO SIHAMA (FORSKAL) AT MANGALORE - Dhulkhed, M H; Ramamurthy, S (Indian Journal of Fisheries, 2011)
The prospects of farming Sillago sihama on the edge of the South Kanam coast have been highlighted in an earlier account (Ramamurthy and Dhulkhed, MS). As a further step, tihe culture of this fish was initiated ’On an experimental blisis to -8:S!s’es its growth: pattern. vh!e results of thisc,study cal’ded out fmm january ,to April 1974’ ar:e pte,sented here